Pelatihan Dasar Analisis Data Menggunakan Google Colab dan Python Untuk Siswa SMA di Wilayah Saboking-king Palembang - Sinta Bella Agustina; Sherly Malini; Ilsa Palingga Ninditama; Yike Diana Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This training program is designed to strengthen digital literacy and basic skills in data analysis for high school students in the Saboking-king area, Palembang, by introducing the Python programming language and the use of Google Colab as a cloud-based programming platform. The approach applied is project-based learning and hands-on experience, which includes planning, implementation, and evaluation stages. Based on the implementation results, the majority of participants showed a good understanding of Python basics and successfully completed the mini-project assignments. The final evaluation revealed an increase in students' motivation and interest to explore programming further. The success of this program confirms that the learning methods and media used are able to support students' understanding of the basic concepts of data analysis. Similar activities are recommended to be implemented in other areas that have limited access to technology.